PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK PRIBADI MUSLIM SISWA - Ma'arif Hidayatullah; Fitriyah Mahdali (Pascasarjana Institut Agama Islam Al-Qolam, 2022)
Teachers are people who educate, guide and take responsibility in forming a Muslim student personality in this case is morality. The teacher is not only someone who stands in front of the class to transfer knowledge, but the teacher is also an example in everyday life both in the community and in the family. While the role is the overall behavior that must be done by the teacher in carrying out his duties as a teacher. This study aims to find out what the roles of Islamic religious teachers are in shaping the Muslim personality of MI Manarul Huda Sukoanyar Wajak student. This research is a field research with a qualitative approach implemented at MI Manarul Huda Sukoanyar Wajak. Aspects in this study are the role of Islamic religious teachers in shaping the Muslim personality of MI Manarul Huda Sukoanyar Wajak students and the behavior of students in the school environment both towards teachers and peers. The author uses data collection techniques by means of observation, interviews, and documentation. In describing the results of the interview, the writer used observation and documentation as reinforcement of the data obtained from the interview results on the role of religious teachers in forming a good Muslim student personality according to shari'ah in this case morals close. The findings in this study are that in educational institutions the role of Islamic religious teachers as motivators, directors, controllers, and guides. In realizing students who have good Muslim personalities, MI Manarul Huda's teacher is very good at carrying out his role. They all become motivators, directors, controllers and guides in the school environment. For example, the teacher leads students to behave respectfully and belonging good manners to the entire existing academic community. Students who violate will be subject to sanctions as a form of preventing the same thing from happening. Keywords: Role of Teacher, Muslim Person